Az érzelemszabályozás interperszonális aspektusai felnőtteknél – egy feltörekvő kutatási irány három modelljének bemutatása - Erika NYITRAI (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica, 2025)
Interpersonal Aspects of Emotion Regulation in Adults – A Presentation of Three Models of an Emerging Research Direction. Emotion regulation is closely intertwined with the fact that we are social beings, experiencing, expressing, and regulating emotions with and through others. Although prevailing approaches to emotion regulation emphasize the importance, even centrality, of interpersonal processes, in the absence of models and measurement tools, the wave of emotion regulation research in the 1990s and 2000s has focused predominantly on intrapersonal processes. Recent efforts to delineate the framework of interpersonal emotion regulation have set the stage for studies in this area. In the present paper, three such frameworks are presented with their associated measurement tools.